SUBSTITUSI TEPUNG AMPAS KEDELAI PADA PRODUK DIMSUM SEBAGAI ALTERNATIF SNACK KAYA SERAT UNTUK PENCEGAHAN DIABETES MELITUS TIPE 2 PADA REMAJA DI MASA PANDEMI COVID-19 - Annisa Tantriana (2021)
Type 2 diabetes mellitus generally suffered in the elderly. However, the prevalence of people with type 2 diabetes mellitus is also increase in children and adolescents. This can be prevented by consuming foods high in dietary fiber. This study aims to examine the effect of substitution of soybean dregs flour on the nutritional content and dietary fiber of dimsum and organoleptic properties in dimsum products as an alternative fiber-rich snack. The method that used in this study is a Completely Randomized Design (CRD) with four levels of treatment for the substitution of soybean dregs flour in dimsum; F0 (0%), F1 (10%), F2 (20%), and F3 (30%). To analyze the result of organoleptic test and the proximate test using the Kruskal-Wallis test and ANOVA test. The results of the organoleptic test stated that there was no significant effect of substitution of soybean dregs flour on the panelist' preference level on the parameters of color, aroma, texture, and taste (p>0.05). The result of the analysis of dietary fiber content of dimsum substituted with soybean dregs flour had a significant effect (p<0.05) on the increase in dietary fiber content of dimsum substituted with soybean dregs flour. The best treatment was found in the formulation F3 (30%) as the selected formula which had a chemical composition per 100 grams; water content (52.41%), ash content (1.31%), protein content (11.46%), fat content (7.09%), carbohydrate content (27.72%), and dietary fiber content (9.87%).